EFEITO DA INCORPORAÇÃO DE NANOPARTÍCULAS DE COBRE EM UM SISTEMA ADESIVO CONVENCIONAL NAS PROPRIEDADES MICROBIOLÓGICAS, MECÂNICAS E ADESIVAS À DENTINA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Objectives: This study evaluated the effect of addition of copper nanoparticles at different concentrations into a simplified etch-and-rinse (ER) adhesive system (Ambar [AM]) on antimicrobial activity (AMA), degree of conversion of adhesives discs (DC-d) and dentin-resin interface (DC-i), the ultimate tensile strength (UTS), 28-day cumulative water sorption (WS), solubility (So) and copper release (CR) as well as immediate (IM) and 1-year (1Y) resin–dentine bond strength (μTBS) and nanoleakage (NL). Methods: Seven experimental adhesive systems were formulated according to the addition of copper nanoparticles (0 [control], 0.0075, 0.015, 0.06, 0.1, 0.5 and 1%) in AM adhesive system. We tested the antimicrobial activity of synthesized adhesives against Streptococcus mutans using agar diffusion assays. For DC-d, specimens were constructed and tested after 24 h for FTIR and micro-Raman spectroscopy. For UTS, specimens were tested after 24 h and 28 days. For WS and So, after specimens build-up, they were stored in water and the properties measured for 28 days. For CR, specimens were stored in 2% nitric acid solution and the properties were measured for 28 days. The occlusal enamel of thirty-five molars was removed and adhesives were applied to dentine surface after 37% phosphoric acid etching. After composite resin build-ups, specimens were longitudinally sectioned to obtain resin–dentine bonded sticks (0.8 mm2). Specimens were tested in tension at 0.5 mm/min in IM or 1Y (μTBS). For NL, 2 bonded sticks from each tooth were prepared and analyzed under SEM in IM or 1Y. For DC-i, 2 bonded sticks were prepared and analyzed under micro-Raman spectroscopy. The μTBS and NL data of each adhesive were subjected to two-way repeated measures ANOVA. For UTS, WS, So, copper release, DC-d and DC-i data of each adhesive were subjected to a one-way ANOVA. Tukey’s post hoc test was used for pair-wise comparisons (α = 0.05). Results: The addition of copper nanoparticles provided antimicrobial properties to the adhesives at all concentrations (p < 0,05), and did not influence UTS, WS and SO (p > 0.05). Higher CR was observed in adhesives with higher concentration of copper nanoparticles (p < 0.05). The addition of 1% of copper nanoparticles decreased the DC-d and DC-i significantly. After 1Y, significant reductions of μTBS and increases of NL were observed in the control group (p < 0.05). Reductions of μTBS and increase of NL over time were not observed for copper-containing adhesives.Conclusions: The addition of copper nanoparticles in concentrations up to 0.5% in the simplified ER Ambar adhesive system may be an alternative to provide antimicrobial properties, increase the long-term stability of resin–dentine interfaces, 12 without reducing adhesives’ mechanical properties evaluated.
Effect of inclusion of copper nanoparticles in etch and rinse adhesive systems on microbiological and mechanical properties, and the durability of resin–dentine interfaces
Keywords: dentina; adesivos convencionais; resistência de união; grau de conversão; nanoinfiltração; resistência a tração; sorção e solubilidade; liberação de cobre; atividade antimicrobiana; dentin; etch-and-rinse; adhesives; resin–dentine bond strength; degree of conversion; nanoleakage; ultimate tensile strength; water sorption and solubility; copper release; antimicrobial activity; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA